ANALYSIS OF MARKETING BUSINESS STRATEGY IN ISLAMIC BUSINESS ETHICS: A QUALITATIVE STUDY OF TURUBUK MSME ACTORS IN MARGASARI, KARAWANG DISTRICT - Budi Adi Saputra; Iis Supriyati (International Journal of Multidisciplinary Reseach, 2026)
A distinctive and popular MSME in Karawang District is the turubuk MSME. Turubuk itself is a unique and typical plant in Karawang Regency. Although it has great potential in maintaining the wheels of the economy, it is not impossible that MSMEs often encounter obstacles in their operations where many MSME business actors are unable to survive long in running their businesses, indicated by a lack of ability to manage business strategies. This study aims to analyze the marketing strategy from the perspective of Islamic business ethics carried out by Warung Tuang as one of the turubuk MSMEs in Margasari Village. From this study, it is hoped that it can formulate significant obstacles for evaluation and better business development in the future. By using a descriptive qualitative method, the results of the study indicate that first, based on the analysis of business development carried out by Warung Tuang, which is one of the MSMEs with a sales orientation of various typical processed products from Karawang Regency, namely the turubuk menu always prioritizes the principles of justice and honesty. Second, when viewed from a marketing perspective, the obstacle in its operations is that Warung Tuang still uses simple word-of-mouth promotion methods. Apart from that, another obstacle is the lack of marketing networks which narrows the gap for business owners to be able to further develop their productivity.